Home-Processed Red Beetroot (Beta vulgaris L.) Products: Changes in Antioxidant Properties and Bioaccessibility - Guldiken, Burcu; Toydemir, Gamze; Nur Memis, Kubra; Okur, Sena; Boyacioglu, Dilek; Capanoglu, Esra (MDPI AG, 2016)
In this study, the effects of home-processing on the antioxidant properties and in vitro bioaccessibility of red beetroot bioactives were investigated. For this purpose, fresh red beetroot and six different home-processed red beetroot products—including boiled, oven-dried, pickled, pureed, juice-processed, and jam-processed—were analyzed and compared for their total phenolic (TP) and total flavonoid (TF) contents, total antioxidant capacities (TAC), and individual anthocyanin contents. In addition, bioaccessibility of red beetroot antioxidants was determined using an in vitro simulated gastrointestinal digestion method. Dried, pureed, and fresh red beetroot samples had the highest TP, TF, and TAC values, which were 347 ± 23 mg gallic acid equivalent (GAE)/100 g, 289 ± 53 mg rutin equivalent (RE)/100 g, 3889 ± 982 mg trolox equivalent antioxidant capacity (TEAC)/100 g, respectively. The in vitro digestion method revealed the highest recovery for TP (16%) and TAC (1.3%) in jam. This study provides comparative data to evaluate the effects of various home-processing techniques on antioxidant potential of red beetroot products.
Keywords: Flavonoids; Biological Products; Phenols; Plant Extracts; Beta vulgaris; red beetroot; Beta vulgaris L.; home-processing; antioxidant; betalain; in vitro digestion; bioaccessibility; Plant Roots; Article; Antioxidants